Developing mobile learning as ecology practical tool using three-layer observation framework - Rizki Agung Sambodo; Baskoro Adi Prayitno; Puguh Karyanto; Eka Sulistyowati (University of Muhammadiyah Malang, 2018)
Developing a practical tool in ecology that addresses the challenge of transferring the ecologicalconcept systematically has become an essential factor in achieving a better understanding of the teaching process. Three-layer Observation Framework (TlOF) is one of the best methods that can be adopted in designing practical work in ecology since its power in providing a step-by-step concept reconstruction. This research aimed to develop a sample of practical work in ecological teaching and learning based on the TlOF. This research followed the ADDIE method in developing the product with some modifications. The research focus was set to gain product’s appropriateness from validators and users. The developed product was tested in Biology Education Department at the State Islamic University of Sunan Kalijaga, Yogyakarta in order to collect responses for further product improvement. The results of the appropriateness test from three validators showed that the developed product is “very good” with an average score of 81.8. During the performed preliminary test by users, as high as 82.5 was achieved. It means that the developed product gained a good perception from the respondents. According to the results, TlOF-based mobile learning the practical tool is the potential to become an alternative media in improving practical work in term of encompassing ecological concepts.